2023
DOI: 10.1136/bmjresp-2023-001684
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status and chronic obstructive pulmonary disease risk: a prospective UK Biobank study

Abstract: BackgroundLow vitamin D status has been linked to an increased risk for various inflammatory diseases. Conflicting results have been reported regarding chronic obstructive pulmonary disease (COPD). This study aims to investigate the associations of serum 25-hydroxyvitamin D (25(OH)D) concentrations with COPD risk and survival.MethodsWe included 403 648 participants with serum 25(OH)D measurements and free of COPD at baseline from UK Biobank. Follow-up was until 30 September 2021. Multivariable-adjusted cox reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…In accordance with the American Association of Clinical Endocrinologists, vitamin D deficiency is defined as a serum level of 25-hydroxyvitamin D (25(OH)D) lower than 75 nanomolar per liter (nmol/L) [ 70 ]. By this definition, as much as 23% of the United States population is at risk of vitamin D deficiency [ 71 ]; vitamin D deficiency is frequently identified in patients with COPD [ 72 , 73 , 74 , 75 , 76 ]. The etiology of this deficiency in COPD seems to be multifactorial, including poor dietary intake [ 77 ], reduced exposure to sunlight [ 77 ], catabolism by common medications prescribed for the management of COPD (i.e., glucocorticoids) [ 77 ], or the effects of comorbid conditions such as chronic kidney disease [ 77 ].…”
Section: Vitamin Dmentioning
confidence: 99%
See 4 more Smart Citations
“…In accordance with the American Association of Clinical Endocrinologists, vitamin D deficiency is defined as a serum level of 25-hydroxyvitamin D (25(OH)D) lower than 75 nanomolar per liter (nmol/L) [ 70 ]. By this definition, as much as 23% of the United States population is at risk of vitamin D deficiency [ 71 ]; vitamin D deficiency is frequently identified in patients with COPD [ 72 , 73 , 74 , 75 , 76 ]. The etiology of this deficiency in COPD seems to be multifactorial, including poor dietary intake [ 77 ], reduced exposure to sunlight [ 77 ], catabolism by common medications prescribed for the management of COPD (i.e., glucocorticoids) [ 77 ], or the effects of comorbid conditions such as chronic kidney disease [ 77 ].…”
Section: Vitamin Dmentioning
confidence: 99%
“…Vitamin D deficiency has been identified as a risk factor for the development of COPD [ 72 , 78 , 79 ], specifically levels lower than 32 nmol/L, which have been associated with a 23% increased risk of developing COPD [ 72 ]. Multiple studies have found that vitamin D deficiency is linked with poor lung function in patients with COPD (GOLD stage I–IV) as measured by FEV 1 [ 76 , 80 ] and FVC [ 76 , 77 ].…”
Section: Vitamin Dmentioning
confidence: 99%
See 3 more Smart Citations